International Consensus Guidelines parameters for the prediction of malignancy in intraductal papillary mucinous neoplasm are not properly weighted and are not cumulative. Issue 10 (30th July 2014) - Roch, Alexandra M.; Ceppa, Eugene P.; DeWitt, John M.; Al‐Haddad, Mohammad A.; House, Michael G.; Nakeeb, Atilla; Schmidt, C. Max
Abstract Background The International Consensus Guidelines (ICG) stratify risk for malignancy in patients with intraductal papillary mucinous neoplasm (IPMN) into three progressive categories according to whether patients show 'no criteria', 'worrisome features' (WFs) or 'high‐risk stigmata' (HRS). Objectives This study was conducted to test the hypothesis that type (clinical versus radiological) and quantity of ICG WFs and HRS carry unequal weight and are not cumulative in the prediction of risk for malignancy or invasiveness in IPMN. Methods A retrospective review of a prospectively maintained database of patients who underwent surgical resection for IPMN at a single, university‐based medical centre during 1992–2012 was performed. Differences that achieved a P‐value of <0.05 were considered significant. Results Of 362 patients, 340 were eligible for entry into the study and were categorized as demonstrating no criteria (n = 70), WFs (n = 185) or HRS (n = 85). Patients in the WFs group had higher rates of malignant and invasive IPMN than those in the no‐criteria group [26.5% versus 4.3% (P < 0.0001) and 15.7% versus 4.3% (P = 0.02), respectively]. Patients in the HRS group had higher rates of malignant and invasive IPMN than those in the WFs group [56.5% versus 26.5% (P = 0.0001) and 42.4% versus 15.7% (P = 0.0001), respectively]. When radiological parameters only were considered for WFs versus HRS, no difference was found in rates of malignant or invasive IPMN. By contrast, when clinical parameters only were considered, patients in the HRS group had higher rates of malignant or invasive IPMN [66.7% versus 8.1% (P = 0.04) and 66.7% versus 2.7% (P = 0.01), respectively]. There was no stepwise increase in rates of malignant or invasive IPMN with the number of WFs. However, patients with only one WF had a lower risk for malignancy than patients with two or more WFs. Conclusions The type and quantity of ICG WFs and HRS carry unequal weight and are not cumulative in the prediction of risk for malignancy or invasiveness in IPMN.